Protocolo para caracterización de bacterias causantes de mastitis clínica y subclínica en fincas lecheras de la sabana de Bogotá (2021)
In previous studies, the presentation of mastitis in the savannah of Bogota has been identified as problematic. Mastitis is an inflammatory reaction of the mammary gland that causes physical and chemical alterations in milk, there are two forms of presentation: clinical and subclinical mastitis.